Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


   ={(a sec A+ b tan A)+ (a tan A+ b sec A)}{(a sec A+ b tan A)-(a tan A+ b sec A)}
   ={(a+b) sec A+(a+b) tan A}*{(a-b) sec A- (a-b) tan A}
   =(a+b)(sec A+ tan A)*(a-b) (sec A -tan A)
   = (a+b) (a-b) (sec A +tan A)(sec A- tan A)
   =a² - b²
0 0 0
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts